PENERAPAN APLIKASI TES BEBRASIS KOMPUTER (CBT) UNTUK MEMBANTU PERAN GURU DAN SISWA DALAM MELAKSANAKAN UJIAN - Dian Rahadian; Andri Suryadi; Dian Nurdiana; Siti Husnul Bariyah; Iman Nasrulloh; Demmy Dharma Bakti; Kuntum Annisa; Yuniar Purwanti (Jurnal Pekemas, 2018)
Based on the Republic of Indonesia Minister of Education and Culture Regulation Number 4 of 2018 concerning Assessment of Learning Outcomes by the Education Unit and Assessment of Learning Outcomes by the Government, the implementation of the National Examination is prioritized through the computer-based national examination (UNBK). This is a problem in some schools that will implement computer-based national exams, especially in Garut district. Based on the results of a survey conducted by a team at several schools in Garut regency, several problems were found such as lack of infrastructure in schools, lack of knowledge about computers in students, lack of applications that could familiarize students and teachers in examinations so students were a little awkward when facing National exam. Therefore, it is necessary to have an application that can help students, teachers, and schools get used to computer-based exams. The methods used in this service are (1) Training / Workshop; (2) Dialogue, Installation, and Simulation; (3) Application Testing (4) Evaluation. Supporting Tools These activities include Infocus and Screen, Laptop, Stationery, and KIT training. Based on the results and discussions that have been conducted, it can be concluded that community service activities with the title of application of computer-based test (CBT) application to help the role of teachers and students in carrying out the tests run well and are useful for users. This can be proven by evaluation of 4 types, namely this application can be useful (usefulness), ease in use (ease of use), ease of learning (ease of learning) and satisfaction in using (satisfaction)